THE ROLE OF EXTRACURRICULAR ACTIVITIES IN FOSTERING YOUTH RESPONSIBILITY AND LEADERSHIP: A LITERATURE REVIEW - Sri Andayani (STIT Pringsewu, 2025)
This study aims to explore the relationship between participation in extracurricular activities and the development of responsibility and leadership among high school students. Using a qualitative approach involving observations and interviews with active students, the research reveals that involvement in extracurriculars significantly enhances social skills, decision-making ability, and self-awareness. Furthermore, such engagement provides real opportunities for students to practice leadership in a supportive context. The findings highlight the vital role of extracurricular programs in shaping character and leadership competence in the younger generation.